Enhancing vibration measurements by Mössbauer effect - Pasquevich, Gustavo Alberto (2014)
The measurement of the Mössbauer effect in a system excited with a periodic perturbation can provide information about it. For that purpose, the Mössbauer absorption of a source-absorber set which hyperfine parameters are well known, is measured at a constant relative velocity (i.e. at a defined spectral energy). The resulting Mössbauer absorption periodic signal provides information of the sample ac perturbation response. This approach has been used time ago to measure small tympanic vibrations (mechanical perturbations). In this work we present an extension of the vibration experiments, by measuring them at various absorber-source relative velocities within a constant-velocity strategy. As a demonstration test, the frequency response of a piezoelectric diaphragm in the 100 Hz-5 kHz range is obtained with a custom electronic counter. The experiments are performed using a 57Co source and a stainless steel 25 um foil absorber fixed to a piezoelectric diaphragm. Phase shifts and amplitude vibrations with velocities in the range from 1.5 um/s to 20 mm/s are well characterized, extending the linearity limit well beyond the earlier suggested one of 1 mm/s.